Monitoreo de la implementación del programa Chile Crece Contigo en el embarazo: 2008 - 2011. - Atalah S., Eduardo; Cordero V., Miguel; Quezada L., Susana; Carrasco F., Ximena; Romo M., Marcela; Guerra Z., María Elizabeth (Revista Chilena de Obstetricia y Ginecología)
Objective: To assess the degree of implementation of the activities of Chile Crece Contigo in pregnancy and childbirth in the 29 country's health services. Method: Analysis of DEIS databases, Ministry of Health 2008 and 2011 by Health Services. Median and percentiles were analyzed at psychosocial risk in pregnant women, comprehensive home visits, mothers participate in educational workshops, childbirth accompanied and early bonding and changing during the study period. Depending on the magnitude of the changes generated a new indicator that allowed classiication of Health Services in tertiles, the highest tertile considering those with more positive changes. Results: prenatal entered nearly 200,000 women each year, approximately 80% of all pregnant women in the country. We observed a signiicant increase of 16-22 percentage points for all variables studied (p<0.005), except home visits to pregnant women in psychosocial risk decreased from 1.6 to 1.1 (p<0.001), with important variations by Health Services. Conclusion: There has been a major effort to modernize the Program for Women and improving prenatal care, childbirth and postpartum, although not relected in health indicators. The differences in behavior Health Services offers the opportunity to deepen the analysis of the causes that explain and the ability to deine strategies to achieve better results.